The Turks in Popular Poetry Melhoun in Algeria. Borrowings and Representations - DELLAÏ Ahmed-Amine (Turath, 2023)
The oldest text of poetry in the Algerian language known as Melhoun poetry that has come down to us dates from the 16th century; therefore, the appearance of this art in our region coincided exactly with the beginnings of the Turkish regency, and its texts have, quite naturally, kept the linguistic, historical, and mental traces of three centuries of Ottoman presence.